Persfektif Patologi Sosial Mengenai Fenomena Pembegalan di Provinsi Bengkulu - Praditya, Arga Dwi (Badan Koordinasi Kegiatan Kesejahteraan Sosial, 2024)
The purpose of writing this article is to describe and find out about people's perspectives on Pembegalan, which some time ago shocked the social media universe, precisely in Bengkulu City itself. The writing of this article uses a qualitative method with a narrative approach. In the research conducted, information was obtained that the robbery was carried out by a group of teenagers who were underage. This research also uses data collection techniques using literature review analysis techniques. Based on the data obtained, it shows that there is a relationship between parenting patterns and this case. In addition, the results showed that 100% of the community's perspective on this robbery case was very troubling and detrimental to every group. In addition, the community also has the perspective that this robbery occurred as a result of wrong parenting, the environment, the family and even the free association that is rampant today.